The Use Of Personal Protective Equipment (PPE) Masks For Visitors At DR Kariadi Hospital Semarang In The Next Normal Era - Linawati Neny Yunitasari; Yustina Denik Risyanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Hospitals are complex health care facilities and provide health care services aimed at improving the health of patients or clients and maintaining the health of hospital visitors. Visitors play a role in the transmission of diseases, particularly the Covid-19 virus, if they do not wear PPE masks when in contact with patients. The purpose of the study was to determine and understand the use of PPE masks for visitors at Dr Kariadi Hospital Semarang in the Next Normal Era. The method used is descriptive qualitative research method with data explanation analysis method. This research data collection method uses semi-structured interviews. Participants in this study were selected using purposive technique. The total number of participants was four, the participants were doctors, nurses and visitors. The findings of this study, the four participants said that visitors at Dr Kariadi Hospital Semarang wear PPE masks when someone is supervising and visitors' awareness of wearing PPE masks is influenced by age, knowledge and education factors.